2015
DOI: 10.1007/s10653-015-9699-7
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water quality and chronic kidney disease of unknown etiology (CKDu): synergic effects of fluoride, cadmium and hardness of water

Abstract: High prevalence of chronic kidney disease of unknown etiology (CKDu) in some regions of the world is suspected mainly due to a toxin-mediated renal failure. We examined the incidence of CKDu and potable chemical water quality in a CKDu-affected region. This region has been identified as a high-risk zone for CKDu (location: latitude: 8.3500°-9.0000°, longitude: 80.3833°-81.3000°, North Central Province, NCP, Sri Lanka) by the World Health Organization (WHO). However, within this macro-region, small pockets of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 31 publications
4
85
2
1
Order By: Relevance
“…suggested that hard water could enhance the cytotoxic properties of fluoride 79 . Undeniably, fluoride levels in drinking water from endemic regions are above WHO safe levels for tropical countries80, 81; however, adjoining farms have not seen significant CKD u 82 . Other theories include the formation of fluoro-aluminium complexes when boiling fluoride-rich water in aluminum kettles (often constructed from discarded car engines).…”
Section: Itai-itai Diseasementioning
confidence: 99%
“…suggested that hard water could enhance the cytotoxic properties of fluoride 79 . Undeniably, fluoride levels in drinking water from endemic regions are above WHO safe levels for tropical countries80, 81; however, adjoining farms have not seen significant CKD u 82 . Other theories include the formation of fluoro-aluminium complexes when boiling fluoride-rich water in aluminum kettles (often constructed from discarded car engines).…”
Section: Itai-itai Diseasementioning
confidence: 99%
“…Studies have analyzed the amount of trace and ultra trace elements in drinking water and have found moderate to high levels of fluoride in affected regions [29]. Wasana et al [30] found strong relation between synergistic effects of fluorine, cadmium, and hardness of drinking water and prevalence of CKDu. Dharma-wardana et al [31] hypothesize that CKDu in the NCP is linked with fertilizer runoff into the river systems from agricultural activity in the central hills which increases the ionicity of the drinking water which has potential to further damage the protein structures in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that there is some correlation between fluoride in drinking waters and the occurrence of CKDU. However, there are no evidence to confirm that fluoride alone is causing CKDU except that two reports showing excess fluoride and calcium together damaging kidneys of laboratory mice [40].…”
Section: Kinetic Studiesmentioning
confidence: 99%